2021
DOI: 10.3390/ani11051328
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite-Based Genetic Characterization of the Indigenous Katjang Goat in Peninsular Malaysia

Abstract: The Katjang goat is the only indigenous domestic goat breed in Malaysia. Following a national baseline survey from 2001 to 2002, this breed was reported to the FAO as being at risk of extinction. In this study, 36 microsatellite markers were screened, and 25 polymorphic markers were used to analyze the genetic structure of the Katjang goat breed in Peninsular Malaysia. A sample set of data derived from another 10 populations from three published research studies was used as an outgroup for an inter-population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The SNP-based estimates of genetic variation are, however, lower than those obtained using microsatellite markers, e.g., Chinese goat breeds (H E between 0.6433 and 0.806) [34,35], Malaysian goats (H E between 0.51 and 0.66) [36] and Canary Island goats (H E between 0.287 and 0.842). However, the differences observed are likely due to the nature of the mutation process in the two types of markers versus SNPs, and to the different technical requirements of microsatellite vs. SNP scoring.…”
Section: Discussionmentioning
confidence: 82%
“…The SNP-based estimates of genetic variation are, however, lower than those obtained using microsatellite markers, e.g., Chinese goat breeds (H E between 0.6433 and 0.806) [34,35], Malaysian goats (H E between 0.51 and 0.66) [36] and Canary Island goats (H E between 0.287 and 0.842). However, the differences observed are likely due to the nature of the mutation process in the two types of markers versus SNPs, and to the different technical requirements of microsatellite vs. SNP scoring.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, the Boer goats had higher RT than their Katjang counterparts. Katjang is considered an indigenous breed of Malaysia ( Devendra, 1987 ) and can withstand the local climatic conditions ( Ernie Muneerah et al, 2021 ). Indigenous breeds thrived well in poor forage and stressful situations compared to imported and crossbred animals (Akinyi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of genetic structure studies was shown by ErnieMuneerah et al (2021) following the example of the endangered, only native Malaysian Katjang goat. This breed is the only native domesticated goat in Malaysia and is perfectly adapted to the local environment, but such low genetic diversity (very low Ho=0.29, high FIS=0.46) may result in a risk to its future existence if not properly maintained and protected to prevent further genetic erosion of this breed.…”
mentioning
confidence: 99%